A Polymorphic 3’UTR Element in ATP1B1 Regulates Alternative Polyadenylation and Is Associated with Blood Pressure - Prasad, Megana K.; Bhalla, Kavita; Pan, Zhen Hua; O’Connell, Jeffrey R.; Weder, Alan B.; Chakravarti, Aravinda; Tian, Bin; Chang, Yen-Pei C. (PloS one, 2013)
Although variants in many genes have previously been shown to be associated with blood pressure (BP) levels, the molecular mechanism underlying these associations are mostly unknown. We identified a multi-allelic T-rich sequence (TRS) in the 3'UTR of ATP1B1 that varies in length and sequence composition (T22-27 and T12GT 3GT6). The 3'UTR of ATP1B1 contains 2 functional polyadenylation signals and the TRS is downstream of the proximal polyadenylation site (A2). Therefore, we hypothesized that alleles of this TRS might influence ATP1B1 expression by regulating alternative polyadenylation. In vitro, the T12GT 3GT6 allele increases polyadenylation at the A2 polyadenylation site as compared to the T23 allele. Consistent with our hypothesis, the relative abundance of the A2-polyadenylated ATP1B1 mRNA was higher in human kidneys with at least one copy of the T12GT 3GT6 allele than in those lacking this allele. The T12GT 3GT6 allele is also associated with higher systolic BP (beta = 3.3 mmHg, p = 0.014) and diastolic BP (beta = 2.4 mmHg, p = 0.003) in a European-American population. Therefore, we have identified a novel multi-allelic TRS in the 3'UTR of ATP1B1 that is associated with higher BP and may mediate its effect by regulating the polyadenylation of the ATP1B1 mRNA.